2022
DOI: 10.3389/fcell.2022.783762
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal Recessive Cerebellar Atrophy and Spastic Ataxia in Patients With Pathogenic Biallelic Variants in GEMIN5

Abstract: The hereditary ataxias are a heterogenous group of disorders with an increasing number of causative genes being described. Due to the clinical and genetic heterogeneity seen in these conditions, the majority of such individuals endure a diagnostic odyssey or remain undiagnosed. Defining the molecular etiology can bring insights into the responsible molecular pathways and eventually the identification of therapeutic targets. Here, we describe the identification of biallelic variants in the GEMIN5 gene among sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 50 publications
1
18
0
Order By: Relevance
“…The presence of Gemin5 variants clustered in conserved residues of the dimerization domain, which provides a platform for protein–protein/RNA interactions ( Moreno-Morcillo et al, 2020 ), reinforces the biological relevance of the TPR-like module for Gemin5 function. Fully consistent with this hypothesis, Gemin5 biallelic variants have been recently associated with cerebellar atrophy and spastic ataxia in several human patients ( Saida et al, 2021 ; Rajan et al, 2022 ). The phenotypic differences observed among individuals carrying similar but nonidentical substitutions in Gemin5 protein remain to be understood as the number of patients affected by this novel disease increase.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…The presence of Gemin5 variants clustered in conserved residues of the dimerization domain, which provides a platform for protein–protein/RNA interactions ( Moreno-Morcillo et al, 2020 ), reinforces the biological relevance of the TPR-like module for Gemin5 function. Fully consistent with this hypothesis, Gemin5 biallelic variants have been recently associated with cerebellar atrophy and spastic ataxia in several human patients ( Saida et al, 2021 ; Rajan et al, 2022 ). The phenotypic differences observed among individuals carrying similar but nonidentical substitutions in Gemin5 protein remain to be understood as the number of patients affected by this novel disease increase.…”
Section: Discussionsupporting
confidence: 54%
“…The mutant R1016C in the individual of case 1 is found in compound heterozygosity with a 5′ splice variant in intron 4 that is predicted to produce a truncated protein, suggesting that the R1016C mutation individually is crucial for the activity of Gemin5 in the cellular environment. In addition, the R1016C mutation has been detected in unrelated patients ( Rajan et al, 2022 ), supporting an overall negative effect in protein function. Thus, the observed destabilizing effect of mutant D1019E in vitro, together with the negative effects of R1016C in living cells, strongly suggest that substitutions in the loop α12-13 of the TPR-like moiety have a negative impact on protein dimerization.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Consistent with this notion, this protein participates in various cellular processes, including tissue regeneration [ 7 ], recognition of 7S RNA Signal Recognition Particle (SRP) [ 8 ], trans-splicing [ 9 ], and translation control [ 10 ]. In further support of the critical activities of this ubiquitously expressed protein for cell growth, recent studies showed that human Gemin5 variants cause developmental disorders presumably due to decreased levels of endogenous Gemin5 protein [ 11 14 ], summing up to the observation that a null KO mouse is embryonic lethal [ 12 ], as well as in zebrafish and Drosophila [ 13 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Gemin5 biallelic variants were recently linked with human neurodevelopmental disorders, perturbing distinct pathways as compared to defects in the SMN protein causing spinal muscular atrophy (SMA) [22] , [23] , [24] , [25] . Dimerization defects in Gemin5 variants described in patients with neurological disorders resulted in the loss of factors connected to RNA processing, translation regulation, and spliceosome assembly [25] , establishing a link between the pathogenic mutations and protein malfunction.…”
Section: Introductionmentioning
confidence: 99%